Incidence of Chondral and Osteochondral Lesions in Ankle Fracture Patients Identified with Ankle Arthroscopy Following Rotational Ankle Fracture - Emilie Williamson MD; Kevin Rosas MD; John Dankert; James P. Toale; Eoghan T. Hurley MB BCh BAO; Kenneth Egol; John G. Kennedy MD, FRCS(Orth) (Foot & Ankle Orthopaedics, 2020)
Category: Ankle; Trauma Introduction/Purpose: It is controversial whether routine arthroscopy is beneficial at the time of ankle fracture fixation. This may be, in part, due to sparse information regarding the incidence of chondral injury in the setting of ankle fractures.The purpose of this study is to systematically review the incidence of chondral injures in patients with ankle fractures and to further characterize intra-articular chondral injuries of the talus, tibial plafond, medial malleolus, and lateral malleolus in patients who undergo ankle arthroscopy following an ankle fracture. Methods: The literature search was performed based on the PRISMA guidelines. Studies evaluating the incidence of chondral lesions at the time of arthroscopy for ankle fractures were included. The incidence of intraarticular chondral lesions was recorded, as well as location within the ankle, ankle fracture type, time of arthroscopy, characterization of chondral injury, complications, and outcome if available. All statistical analyses were carried out with statistical software package SPSS 24.0 (SPSS, Chicago, IL, USA). Multiple comparisons were used to compare incidence rates of chondral injury based on Weber classification, malleolar fracture type, and Lauge-Hansen classification, using Pearson chi-square test. For all analyses, p < 0.05 was considered statistically significant. Results: Fifteen studies with 1,355 ankle fractures were included. Of those ankles, 738 demonstrated evidence of chondral or osteochondral lesion (54.5%). Overall, 648 ankles had chondral lesions on the talus (47.8%), 207 ankles had lesions on the tibial plafond (15.3%), 165 has lesions of the lateral malleolus (12.2%), and 133 had lesions of the medial malleolus (9.8%). Weber C group had significantly higher incidence than Weber A group (p=0.015). Trimalleolar and isolated lateral malleolar fracture groups had significantly higher incidence of chondral injury than bimalleolar and isolated medial malleolar fracture groups (p<0.001). A significant difference was found in occurrence rate of chondral injury among Lauge-Hansen classification, with supination-adduction having the lowest incidence (p=0.001). Conclusion: Our study found a high incidence of intra-articular chondral lesion in the setting of ankle fractures as demonstrated by arthroscopy, with more than half of all patients having a chondral lesion. Talar lesions were most common. This study may help direct greater attention to the Talus as a source of chondral injury particularly in higher grade fracture patterns.